2012
DOI: 10.1002/j.1532-2149.2012.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal summation of heat pain modulated by isometric exercise

Abstract: BACKGROUND Little is known about the effects of isometric exercise on temporal summation of heat pain. Thus, the purposes of study 1 and study 2 were to examine the influence of exhaustive and non-exhaustive isometric exercise on temporal summation of heat pain in men and women. METHODS Forty-four men and 44 women (mean age = 20 yrs) completed an informed consent document and a packet of questionnaires. Ten heat pulses were applied to the thenar eminence of the dominant hand using a standardized temporal sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 34 publications
5
39
0
Order By: Relevance
“…Currently, the results from the limited number of studies which have examined sex differences in EIH are equivocal. 28,39,40,68 The results from the present study indicated no significant differences in EIH between men and women, but women were tested during the follicular phase of their menstrual cycle. These results are in agreement with the only other EIH study to control for menstrual cycle phase which also reported no significant sex differences in EIH when women were tested during the follicular phase of their menstrual cycle.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…Currently, the results from the limited number of studies which have examined sex differences in EIH are equivocal. 28,39,40,68 The results from the present study indicated no significant differences in EIH between men and women, but women were tested during the follicular phase of their menstrual cycle. These results are in agreement with the only other EIH study to control for menstrual cycle phase which also reported no significant sex differences in EIH when women were tested during the follicular phase of their menstrual cycle.…”
Section: Discussionmentioning
confidence: 44%
“…A power analysis was performed to estimate an optimal sample size for detecting a potential difference between men and women in the effects of naltrexone on EIH using a repeated measures design, with an alpha of 0.05, a power of 0.80, and a medium effect of 0.50. 39,76 Results from the analysis indicated that 44 participants (22 women and 22 men) would be needed for the study; however, sample size was increased in anticipation of potential subject attrition. Sixty healthy adults (30 women, 30 men) between the ages of 18–40 yrs without a history of major medical problems or routine use of medications were recruited for this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise can reduce the perception of pain-eliciting mechanical, thermal, and electrical stimuli [4,5,6,7,8,9,10]. Although the most studied form of exercise for pain reduction is aerobic, evidence has shown that submaximal isometric contractions engage a centralized pain inhibitory response such that the analgesic effect is not constrained to the exercising limb [5,10].…”
Section: Introductionmentioning
confidence: 99%
“…Demonstrating that short-duration submaximal contractions can influence the perception of pain that is simultaneously experienced in another limb is important because this approach may translate to clinical rehabilitation settings. However, to date, most studies have examined pain perception before and after relatively long isometric contractions [4,5,7]. Evidence for an analgesic effect when acute painful stimuli and acute isometric contractions occur simultaneously and for a similar amount of time is limited to a single study that showed a lateralized analgesic effect at one submaximal force level [10].…”
Section: Introductionmentioning
confidence: 99%